EFEKTIFITAS PENCARIAN KOST DENGAN SISTEM INFORMASI BERBASIS ANDROID - Ria Manurung (Electro Luceat, 2020)
Android-based smartphones are opensource for developers to create or develop new applications. The existence of smartphones really helps users to get information and fulfill various needs more quickly and easily, including in terms of finding a boarding house. Based on results of discussion in this study, it can be concluded that Android-based Boarding Information System is very effective in finding boarding houses in Purwokerto. This performance has been tested based on Dimension of Quality for Goods by having a good quality product and suitable for use by general public. This is evidenced by product test results with an average value of 84.90, which means that it is greater than passing limit value determined by the researcher, namely 75. The results of benefit test that have been carried out to determine the benefits of the system for its users also produce good values, namely: Usefulness = 94.8%, Ease = 94.8%, Efficiency = 95.8% and Accuracy = 93.8%. From results of this benefit test, it can be said that system is felt to be useful and useful for users who will search or view boarding houses in Purwokerto and for boarding providers are also very helpful in providing information on boarding seekers